Isolation of acetylated bile acids from the sponge Siphonochalina fortis and DNA damage evaluation by the comet assay - Patiño Cano, Laura Patricia (2013)
From the organic extracts of the sponge Siphonochalina fortis, collected at Bahía Bustamante, Chubut, Argentina, three major compounds were isolated and identified as deoxycholic acid 3, 12-diacetate (1), cholic acid 3, 7, 12-triacetate (2) and cholic acid, 3, 7, 12-triacetate. (3). This is the first report of acetylated bile acids in sponges and the first isolation of compound 3 as a natural product. The potential induction of DNA lesions by the isolated compounds was investigated using the comet assay in lymphocytes of human peripheral blood as in vitro model. The results showed that the administration of the bile acid derivatives would not induce DNA damages, indicating that acetylated bile acids are nontoxic metabolites at the tested concentrations. Since the free bile acids were not detected, it is unlikely that the acetylated compounds may be part of the sponge cells detoxification mechanisms. These results may suggest a possible role of acetylated bile acids as a chemical defense mechanism, product of a symbiotic relationship with microorganisms, which would explain their seasonal and geographical variation, and their influence on the previously observed genotoxicity of the organic extract of S. fortis.